Zarys historii ewangelizacji Meksyku od XVI do XVII wieku - Tomasz Szyszka, (Annales Missiologici Posnanienses, 2019)
The evangelization of Mexico in the 16th and 17th centuries is a fascinating period in the history of Christianization of the New World. The creative confrontation of the then missionaries (Franciscans, Dominicans, Augustinians, and Jesuits) with local cultures and beliefs and the Spanish conquest system resulted in the development of innovative methods of working with indigenous peoples (catechisms, education, art, hospitality, scientiﬁ c research) and the creation of stable church structures in Mexico.